Effects of salinity on osmoregulation, growth and survival in Asian swamp eel (Monopterus albus) (Zuiew 1793). Issue 3 (4th August 2012) - Pedersen, Pil Birkefeldt Møller; Hansen, Kasper; Houng, Do Thi Thanh; Bayley, Mark; Wang, Tobias
Abstract The Asian swamp eel Monopterus albus is normally considered a freshwater species, but can also occasionally be found in brackish water. It is an obligate air‐breather with highly reduced gills, making its osmoregulation physiology interesting because the gills normally represent the primary site of osmoregulation in teleosts. Being a popular fish for human consumption, the swamp eel is cultured extensively in freshwater ponds in the Mekong Delta of Vietnam. However, very little is known about its salinity tolerance, which is becoming topical due to the increasing salt‐water intrusions into tropical deltas. We therefore studied how increased salinity affects survival, growth, blood pressure, heart rate, blood osmolality and plasma ions. All eels survived prolonged exposure to 5 and 10 g L−1, although plasma osmolality increased significantly at 10 g L−1. Further elevation to 15 and 20 g L−1 was associated with significantly elevated mortality, with a corresponding increase in plasma osmolality and ion con‐centrations. Our results show that swamp eels thrive in 0–10 g L−1 with an optimum growth between 0 and 9 g L−1, indicating that utilization of low saline brackish waters for aquaculture is possible.